2017
DOI: 10.1111/mec.14132
|View full text |Cite
|
Sign up to set email alerts
|

Organic farming increases richness of fungal taxa in the wheat phyllosphere

Abstract: Organic farming is often advocated as an approach to mitigate biodiversity loss on agricultural land. The phyllosphere provides a habitat for diverse fungal communities that are important for plant health and productivity. However, it is still unknown how organic farming affects the diversity of phyllosphere fungi in major crops. We sampled wheat leaves from 22 organically and conventionally cultivated fields in Sweden, paired based on their geographical location and wheat cultivar. Fungal communities were des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 67 publications
6
42
0
2
Order By: Relevance
“…A network analysis revealed that Z. tritici co-occurs negatively with the yeasts Dioszegia, Sporobolomyces , and Cystofilobasidiaceae . A similar analysis of data from our previous study ( Sapkota et al, 2015 ) and data from Karlsson et al (2017) showed similar negative co-occurrence patterns between Z. tritici and several yeasts, thus supporting our results. The relative abundance of Z. tritici and the yeasts was strikingly constant, particularly across the samples from the three leaf positions, but also across cultivars and between GS 69–71 and 75–78.…”
Section: Discussionsupporting
confidence: 91%
“…A network analysis revealed that Z. tritici co-occurs negatively with the yeasts Dioszegia, Sporobolomyces , and Cystofilobasidiaceae . A similar analysis of data from our previous study ( Sapkota et al, 2015 ) and data from Karlsson et al (2017) showed similar negative co-occurrence patterns between Z. tritici and several yeasts, thus supporting our results. The relative abundance of Z. tritici and the yeasts was strikingly constant, particularly across the samples from the three leaf positions, but also across cultivars and between GS 69–71 and 75–78.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have demonstrated that wheat spikes and grains harbour a high diversity of these ascomycetes [36,39,40]. Similar trends have been observed in wheat leaves as Zymoseptoria tritici was found to be the most abundant fungus in later stage leaves [23,41]. This suggests a general increase in abundance of opportunistic or even pathogenic fungi over time in wheat tissues.…”
Section: Discussionsupporting
confidence: 66%
“…The farmers were asked to combine several subsamples into a representative sample of the field. Earlier in the season, in July 2012, wheat leaves were collected from the same fields and a number of additional data were collected at the same time (Karlsson et al, 2017). At the start and end of the transect used for leaf sampling, two 0.25 m 2 squares were laid out and weeds and crop plants in each square were cut and the biomass was separated, dried for 24 h at 105°C and weighed to determine dry mass.…”
Section: Methodsmentioning
confidence: 99%